A Study on Students’ Difficulties in Learning Vocabulary at Grade VIII of MTs Negeri in Padangsidimpuan - Siregar, Fitri Rayani; Zainuddin, Zainuddin (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This study investigated the difficulties faced by eighth-grade students at MTsN Padangsidimpuan in learning English vocabulary. The research revealed that students encountered various challenges, including Pronunciation, Meaning, Spelling, Memorization, Differentiation and Sentence integration. Additionally, the study identified several factors contributing to these difficulties: Lack of engagement and Limited exposure. To address these issues, the research explored pedagogical strategies used by teachers to help students overcome their difficulties. These strategies included Vocabulary tasks, Memorization techniques, Differentiated learning, Active practice, Engaging methods, Dictionary skills. This research highlights the importance of understanding student difficulties in vocabulary learning and implementing effective pedagogical approaches to overcome them. The identified challenges, contributing factors, and teacher strategies provide valuable insights for improving English vocabulary instruction in the context of MTsN Padangsidimpuan and beyond.